Globalisation and productivity growth theory and evidence - Gorg Holger; Greenaway David; Kneller Richard (Hampshire Palgrave Macmillan, 2005)
This volume offers a comprehensive overview of links between international trade, foreign direct investment and productivity growth, providing a series of empirical analyses of these links.
Keywords: Exports; Foreign investments; Globalization-economic aspects; Industrial productivity; International business enterprises